ARISTOLOCHIA BRACTEOLATE RETZ. ATTENUATES HYPERURICEMIA IN A METABOLIC ARTHRITIS RAT MODEL - Yun-peng, Li; Shuang, Wu; Ran, Afou; Xu, Da-yong; Wei, Jing-mei; Zhao, Zi-long (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The leaves of Aristolochia bracteolata Retz. has been documented in the folk medicine literature for its anti-arthritic activity. The target of the research envisaged was to elucidate the activity of A. bracteolata extract on hyperuricemic condition in arthritis rat model. Materials and Methods: Dried and powdered plant leaves were extracted using ether and chloroform. Potassium oxonate was injected intra-articularly to produce arthritis. The hyperuricemic effect, of A. bracteolate was analyzed by studying levels of uric acid in serum as well as in urine of arthritis induced rats. Effects of plant extracts were also studied on BUN (blood urea nitrogen) levels and fraction of uric acid excreted. Results: Results indicate that administration of A. bracteolata presented substantial change in uric acid concentration, augmented by potassium oxonate administration in rats. The reduction in levels of uric acid levels was nearly same as allopurinol. The investigation also revealed that the primary plant extract has nephroprotective effect by enhancing the production of Prostaglandin E2 and Interleukin-1. Histological studies of rat kidney slices indicated the safety of the present plant extract. Conclusion: The crude extract of A. bracteolate can be used to reduce hyperuricemia in metabolic arthritis produced in rat model, without inducing any potential damaging effects.